2017
DOI: 10.1109/tns.2016.2641479
|View full text |Cite
|
Sign up to set email alerts
|

Dark Current Spectroscopy in Neutron, Proton and Ion Irradiated CMOS Image Sensors: From Point Defects to Clusters

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
(85 reference statements)
3
15
0
Order By: Relevance
“…Since the NIEL is unknown in the literature, the DDD cannot be estimated neither. However, as a heavy ion (six protons and six neutrons), due to its large cross section as well as its charge and mass, we expect to have a huge DDD resulting from both nuclear and coulombic interactions [15]. Characterizations have been performed one week after irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the NIEL is unknown in the literature, the DDD cannot be estimated neither. However, as a heavy ion (six protons and six neutrons), due to its large cross section as well as its charge and mass, we expect to have a huge DDD resulting from both nuclear and coulombic interactions [15]. Characterizations have been performed one week after irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we can express the activation energy at room temperature as a function of the energy level into the silicon bandgap as [15] E a (T ) = 0.65 + E.…”
Section: A Characterization Before Irradiationmentioning
confidence: 99%
“…The pre-factor A is proportional to T 2 and estimated to be ln(A)≈36 at 300 K in our studied case, from the experimental value of the divacancy given in [7,17,6].The term ! is commonly named the activation energy needed for one electron to go from the valence band to the conduction band.…”
Section: Calculations Detailsmentioning
confidence: 78%
“…the di-vacancy (2V) and the tri-interstitial (3I). Their properties are analyzed and compared with DC and DC-RTS measurements on CMOS Image Sensors (CIS) [6,7] and DLTS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Raine et al [3] have investigated the single DD damage effects on CISs using simulations based on Geant4. Belloir et al [4] have reported the neutron, proton, and heavy ion radiation effects on the dark current spectroscopy of CISs. Wang et al [5][6][7] have presented results on neutron and γ rays radiation effects on CISs.…”
mentioning
confidence: 99%